Factors Predicting Quality of Bowel Preparation in Monks Undergoing Colonoscopy - Wong-in, Nujira; Wongkongkam, Kessiri; Chanruangvanich, Wallada; Kaosombatwattana, Uayporn (Journal of Thailand Nursing and Midwifery Council, 2025)
Introduction Colonoscopy is an important procedure for diagnosing colorectal cancer. It involves crucial preparation steps, particularly cleaning the colon to free of feces and fecal fluid. This ensures the accuracy of the diagnosis, allowing clear images of the mucosa, polyps, or cancerous lesions inside the colon. Proper preparation also helps minimize potential side effects or complications. Monks receive alms from the public, which can affect the type of food they consume and, consequently, their ability to prepare their colon for the procedure. Quality of bowel preparation is critical, as an inadequate bowel preparation can result in an incomplete procedure and may lead to a rescheduled appointment for a repeat examination. However, simply scheduling monks for hospital stay in advance for bowel preparation may not be sufficient to ensure proper bowel preparation for the colonoscopy. Objectives This study aimed to 1) describe the quality of bowel preparation in monks undergoing colonoscopy, and 2) investigate predictive factors of bowel preparation quality in monks undergoing colonoscopy, including the risk of constipation, pre-operative risks (American Society of Anesthesiologists status classification, ASA class), and dietary fiber intake. Design This study employed a predictive correlational design using Roy’s Adaptation Model as a conceptual framework for the preparation of colonoscopy. The process involves inputs through physiological control mechanisms related to bowel movement regulation and nutritional adaptation to modify the dietary intake in order to reduce fiber in the gastrointestinal system. This entire process collectively influences the quality of bowel preparation. Methodology The participants consisted of 199 monks at a hospital for a colonoscopy between April 2021 and January 2023. They were selected using a purposive sampling based on inclusion criteria: being 20 years or older, undergoing colonoscopy for screening, diagnosis, treatment, or post-surgical follow-up. Those 60 years and older must have a normal cognitive function screened with a Mini-Cog score of > 3. Exclusion criteria included a history of psychiatric disorders, difficulty swallowing, bowel obstruction or occlusion, lower gastrointestinal bleeding, bowel or gastrointestinal resection, and any anatomical abnormalities of the gastrointestinal tract. The research instruments included a Mini-Cog test for screening cognitive impairment, a personal information questionnaire, a clinical information questionnaire, and a constipation risk assessment tool, which had a content validity index (CVI) of .83 and a Cronbach’s alpha coefficient of .93. Additionally, there was a food intake questionnaire prior to the colonoscopy, with a CVI of 1.00, an ASA class pre-operative risk assessment form, and the Boston Bowel Preparation Score (BBPS) with an inter-rater reliability (IRR) of .85. Data were collected through structured interviews and medical record reviews. Descriptive statistics were used for data analysis, and logistic regression was employed to analyze predictive factors for bowel preparation quality in monks undergoing colonoscopy, with a significance level set at .05. Results The participants of 199 monks who underwent colonoscopy had a mean age of 60.8 years (SD = 8.9), with the majority of older adults (66.8%). Approximately 40.2% of them had body mass index (BMI) ranging from 23.00 - 24.99 kg/m², with a mean BMI of 24.2 kg/m² (SD = 1.90). Of the participants, 38.2% had a history of smoking, with a mean smoking duration of 30.00 years (SD = 8.47). Additionally, 27.1% had a history of tea consumption, with a mean duration of 20.00 years (SD = 6.46), while 33.2% had a history of coffee consumption, with a mean duration of 19.00 years (SD = 6.72). Furthermore, 61.8% reported engaging in physical activity. Analysis of clinical data revealed that 44.7% of the 199 participants had underlying medical conditions, with the most common being hypertension (25.1%), followed by gastrointestinal diseases (18.1%). A total of 37.2% had a history of regular medication use, with the most common for antihypertensive medications (23.1%). The most frequently prescribed laxative was Polyethylene Glycol (PEG) at 98.5%. The majority of participants (90.5%) underwent the colonoscopy in the morning on their scheduled appointment day. According to the BBPS, 77.4 % of them had good quality of bowel preparation at a mean of 7.83 (SD=1.83). Logistic regression analysis showed constipation risk (OR 3.496, 95%CI: 2.575 – 7.046, p < .01), ASA class (OR 3.766, 95% CI.:3.508 – 7.239, p < .01) and dietary fiber intake (OR 5.461, 95% CI: 4.921– 8.578, p < .01) together predicted quality of bowel preparation in monks undergoing colonoscopy. These factors can jointly predict the quality of bowel preparation among monks undergoing colonoscopy at 71.3% (Nagelkerke R2=.713, p < .05). Recommendation Nurses can use the study findings to plan strategies for promoting bowel preparation in monks undergoing colonoscopy by assessing pre-operative risk, the risk of constipation, and dietary fiber intake prior to the procedure. Future studies could explore additional factors, such as stool characteristics during bowel preparation and regular medications. Additionally, research could focus on providing guidance and follow-up evaluations, particularly regarding low-fiber diet recommendations during the 3 days prior to hospital admission for effective bowel preparation.